EVALUATION OF KNOWLEDGE OF BIOSAFETY OF HEALTH PROFESSIONALS OF MULTIPROFESSIONAL RESIDENCE OF A HOSPITAL - Nicollau Silva de Souza, Rafaell; Moura Motta Silveira, Fabiana; Maria Silva de Souza, Rafaella; Martins, Alcieros; Cavalcanti, Emidio; Silva de Souza, Wagner (Health and Society, 2023)
The recent concept of biosafety encompasses the set of actions aimed at preventing, minimizing or eliminating risks inherent to research, production, teaching, technological development and service provision activities, aiming to preserve the health of man, animals and the environment . In this context, awareness and permanent education of professionals are also essential, which provides them with conditions to carry out safe work, critical discussions and reflections, update and adoption of correct preventive measures. The objective of the research was to evaluate the knowledge of health professionals from the Multiprofessional Residency of the Instituto de Medicina Integral Professor Fernando Figueira, about biosecurity in the hospital premises. The study was of the descriptive observational epidemiological type through the application of a questionnaire on the topic addressed. The sample consisted of a multidisciplinary population, effectively enrolled in the first and second years of residency (n=83). Of the participants, 89.2% reported being aware of the risks of biosafety, 81.9% walk around the hospital’s internal and external areas wearing the lab coat, 96.4% usually use the lab coat in restaurants and only 34.9% correctly clean the hands in a hospital environment. Insufficient biosafety practices are notorious, which demonstrates a lack of awareness on the part of professionals. Thus, basic and consensual measures are necessary to remedy and/or reduce risks and contamination vectors in hospital sectors by health professionals.